Does changing healthcare use signal opportunities for earlier detection of cancer? A review of studies using information from electronic patient records. (February 2022) - White, Becky; Renzi, Cristina; Rafiq, Meena; Abel, Gary A.; Jensen, Henry; Lyratzopoulos, Georgios
Abstract: Background: It has been proposed that changes in healthcare use before cancer diagnosis could signal opportunities for quicker detection, but systematic appreciation of such evidence is lacking. We reviewed studies examining pre-diagnostic changes in healthcare utilisation (e.g. rates of GP or hospital consultations, prescriptions or diagnostic tests) among patients subsequently diagnosed with cancer. Methods: We identified studies through Pubmed searches complemented by expert elicitation. We extracted information on the earliest time point when diagnosis could have been possible for at least some cancers, together with variation in the length of such 'diagnostic windows' by tumour and patient characteristics. Results: Across twenty-eight studies, changes in healthcare use were observable at least six months pre-diagnosis for many common cancers, and potentially even earlier for colorectal cancer, multiple myeloma and brain tumours. Early changes were also identified for brain and colon cancer sub-sites. Conclusion: Changing healthcare utilisation patterns before diagnosis indicate that future improvements in diagnostic technologies or services could help to shorten diagnostic intervals for cancer. There is greatest potential for quicker diagnosis for certain cancer types and patient groups, which can inform priorities for the development of decision support tools. Highlights: Emerging research has found that healthcare use changes months before eventual diagnosis of cancer. This could identify which tumour or patient groups could be diagnosed sooner, and how much sooner. Our review confirms that patients' healthcare use changes at least six months before diagnosis for many common cancers. Some studies suggested that patients with myeloma, brain tumours, or colorectal cancers could be diagnosed even sooner.